Concurrent validity of the GAITRite electronic walkway and the 10-meter walk test for measurement of walking speed after stroke - Cleland, Brice T. (Gait Posture, 2018)
BACKGROUND: Walking speed is used to assess functional status, predict recovery, prescribe exercise, and track functional progress after stroke. Determining concurrent validity ensures that results from different tests of walking speed can be compared or used interchangeably. The GAITRite electronic walkway and the 10-meter walk test (10MWT) are popular measurement tools of walking speed in the laboratory and in clinical settings, respectively. RESEARCH QUESTION: Do walking speeds in chronic stroke survivors measured with the 10-meter walk test and GAITRite electronic walkway demonstrate concurrent validity? METHODS: 77 participants with chronic stroke performed four trials of 10MWT and four trials of GAITRite—two trials at comfortable walking speed and two trials at maximal walking speed. Intraclass correlations [ICC (3,1), absolute agreement] and Bland-Altman plots were used to assess the relationship between gait speed from these two measures. RESULTS: Walking speed showed poor to good absolute agreement between 10MWT and GAITRite for comfortable walking speed [ICC: 0.77 (95% CI: 0.46, 0.89; P<0.001)] and excellent absolute agreement for maximal walking speed [ICC: 0.94 (95% CI: 0.91, 0.96; P<0.001)]. Mean difference value (systematic bias) was different from 0 for comfortable walking [10MWT was faster; P<0.001 (95% CI: 0.05, 0.10)] but not for maximal walking [P=0.16 (95% CI: −0.01, 0.04)]. Limits of agreement were broad (comfortable walking speed, 0.43; maximal walking speed, 0.37), and there was proportional bias at both speeds whereby participants who walked faster tended to have a faster walking speed during 10MWT vs. GAITRite (comfortable walking speed, R(2)=0.22, P<0.001; maximal walking speed, R(2)=0.08, P=0.01). SIGNIFICANCE: Systematic bias, proportional bias, and broad limits of agreement suggest that caution should be used when comparing walking speeds from 10MWT and GAITRite. It may not be appropriate to use them interchangeably. Conducting 10MWT and GAITRite tests at maximal walking speeds may allow more accurate comparisons between measures.